The Role of Participatory Communication among PNPM Urban Facilitators in Sustaining Community Institutions After the Program’s Termination - Rochmad Effendy; Dodot Sapto Adi; Aryo Prakoso Wibowo; Yuntawati Fristin (Jogjakarta Communication Conference (JCC), 2026)
The post-Reformasi introduction of PNPM marked a shift in Indonesia’s development paradigm toward community-driven approaches. PNPM positioned citizens as active agents across planning, implementation, and evaluation, and framed poverty as rooted in the weakening of moral virtues within community life. Facilitators were therefore tasked with enabling social learning and internalizing PNPM’s values among residents. This literature-based qualitative study examines how participatory development communication contributed to behavioral change and institutional sustainability after PNPM ended in 2016. The findings show that facilitators employed participatory communication characterized by egalitarian dialogue, problem-posing methods, iterative reflection and action (praxis), the development of critical consciousness, and an ethical foundation built on trust and humility. They also practiced authentic communication emphasizing honesty, openness, and compassion. The integration of these approaches—participatory authentic communication—strengthened community empowerment by fostering sincerity, care, and solidarity. These moral foundations helped sustain community institutions such as the Lembaga Keswadayaan Masyarakat (LKM), even after PNPM’s formal termination.